2001
DOI: 10.1067/mtc.2001.116946
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac nociceptive reflexes after transmyocardial laser revascularization: Implications for the neural hypothesis of angina relief

Abstract: Transmyocardial laser revascularization has no significant short-term effect on reflexes mediated by left ventricular receptors with sympathetic afferent fibers in anesthetized dogs. These results indicate that transmyocardial laser revascularization does not acutely interrupt the afferent nerves, which are believed to transmit the perception of anginal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…However, Hirsch et al, 20 using direct electrical as well as chemical neural stimulation techniques, have published data indicating that nonischemic canine myocardium is innervated 30 minutes after holmium:YAG TMR. Similarly, Minisi and colleagues 21 extended these observations by measuring the integrity of the entire sympathetic afferent reflex arc, which they found to be fully functional 45 minutes after holmium:YAG TMR in nonischemic dogs. Whether these discordant results are due to the short time after TMR at which innervation was assessed in the latter studies or to the alternative experimental methods utilized is unclear.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, Hirsch et al, 20 using direct electrical as well as chemical neural stimulation techniques, have published data indicating that nonischemic canine myocardium is innervated 30 minutes after holmium:YAG TMR. Similarly, Minisi and colleagues 21 extended these observations by measuring the integrity of the entire sympathetic afferent reflex arc, which they found to be fully functional 45 minutes after holmium:YAG TMR in nonischemic dogs. Whether these discordant results are due to the short time after TMR at which innervation was assessed in the latter studies or to the alternative experimental methods utilized is unclear.…”
Section: Discussionmentioning
confidence: 87%
“…Whether these discordant results are due to the short time after TMR at which innervation was assessed in the latter studies or to the alternative experimental methods utilized is unclear. As pointed out by Minisi et al, 21 neither TYR‐OH nor C‐11 hydroxyephedrine is specific for cardiac receptors with sympathetic afferent fibers, which are the fibers felt responsible for cardiac nociception and anginal pain. It is noteworthy that it has been well established that TMR invokes an intense inflammatory response in the lased regions, 32 a response that might potentially play a role in the local destruction of nerve fibers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of ventricular receptors, as well as sympathetic afferent fibers (which send painful cardiac stimuli into the brain) would corroborate with this hypothesis. However, this event tends to be temporary because there is evidence of re-innervation after six months [18,19]. Another hypothesis may come from the destruction of the ischemic myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…However, several experimental studies have demonstrated that denervation may indeed play a role in Ho:YAG TMR [50, 51, 52]. Experimental evidence to the contrary was provided in a nonischemic animal model [53]. Regardless of the methodology employed in the laboratory, there is significant evidence of sympathetic denervation following positron emission tomography of Ho:YAG TMR-treated patients [54].…”
Section: Mechanisms Of Tmrmentioning
confidence: 99%